Use the graph that shows the solution to \(f(x)=g(x)\).

\(f(x)={7\over 3} x -3\)

\(g(x)=2^x-4\)

What is the solution to \(f(x)=g(x) \)?

Select **each** correct answer.

\(- {1 \over 2}\)

0

2

3

mindless May 17, 2019

#1**+5 **

Let's look at f(x) to determine which graph is correct.

f(x) = \(\frac73\)x - 3

f(0) = \(\frac73\)(0) - 3 = -3

Since f(0) = -3, the graph of f(x) passes through the point (0, 3)

So we can see that the first graph is wrong, and the second graph is correct.

We can see that...

f(0) = -3 and g(0) = -3 so f(0) = g(0)

f(3) = 4 and g(3) = 4 so f(3) = g(3)

So...

x = 0 is a solution to f(x) = g(x)

x = 3 is a solution to f(x) = g(x)

hectictar May 18, 2019

#2**+1 **

First, find the correct graph.... at x = 0

f(x) = -3 g(x) = -3 This conforms to the SECOND graph.....

NOW, f (x) = g(x) where the graphs intersect....which is at x= .....? (two places)

ElectricPavlov May 18, 2019